2004
DOI: 10.1128/jb.186.2.270-277.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization ofBurkholderia cenocepaciaMutants Deficient in Pyochelin Production: Pyochelin Biosynthesis Is Sensitive to Sulfur Availability

Abstract: The opportunistic pathogen Burkholderia cenocepacia produces the yellow-green fluorescent siderophore, pyochelin. To isolate mutants which do not produce this siderophore, we mutagenized B. cenocepacia with the transposon mini-Tn5Tp. Two nonfluorescent mutants were identified which were unable to produce pyochelin. In both mutants, the transposon had integrated into a gene encoding an orthologue of CysW, a component of the sulfate/thiosulfate transporter. The cysW gene was located within a putative operon enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Although PAPS-reductase has not been demonstrated to be a virulence factor, it is reasonable that it could be a fitness factor under conditions of sulfur limitation. In Burkholderia, it has been shown that sulfur limitation preferentially affects biosynthesis of the siderophore pyochelin over that of cysteine synthesis [41]. Siderophores are known Burkholderia pathogenicity factors and pyochelin is one of a number of endogenous and exogenous siderophores that Burkholderia utilizes, contributing to success in the iron-limiting lung environment [42].…”
Section: Lambda-related Phages Of Burkholderiamentioning
confidence: 99%
“…Although PAPS-reductase has not been demonstrated to be a virulence factor, it is reasonable that it could be a fitness factor under conditions of sulfur limitation. In Burkholderia, it has been shown that sulfur limitation preferentially affects biosynthesis of the siderophore pyochelin over that of cysteine synthesis [41]. Siderophores are known Burkholderia pathogenicity factors and pyochelin is one of a number of endogenous and exogenous siderophores that Burkholderia utilizes, contributing to success in the iron-limiting lung environment [42].…”
Section: Lambda-related Phages Of Burkholderiamentioning
confidence: 99%
“…The opportunistic pathogen B. cenocepacia also produces the siderophore pyochelin and an FptA receptor highly similar (63 % identity, 76 % similarity) to the ferripyochelin receptor from P. aeruginosa (Farmer & Thomas, 2004;Mislin et al, 2006). Fig.…”
Section: B Cenocepacia Is Insensitive To Pyocin S5mentioning
confidence: 99%
“…Tn5 derivatives have been shown to be useful for genetic analysis of members of the genus Burkholderia (Dennis & Zylstra, 1998;Sokol et al, 1999;Farmer & Thomas, 2004;Agnoli et al, 2006). To increase the versatility of these transposons, we inserted a promoterless lac cassette into the unique NotI site of mini-Tn5Cm and mini-Tn5Tp, thereby allowing lacZ to serve as a reporter of transcription originating in genomic DNA flanking the O end of the integrated transposon.…”
Section: Construction Of New Reporter Transposons For Use In Burkholdmentioning
confidence: 99%
“…Isolation of B. cenocepacia mutants in which production of both ornibactin and pyochelin is decreased or abolished B. cenocepacia strain 715j produces the siderophores ornibactin and pyochelin (Darling et al, 1998;Visser et al, 2004;Farmer & Thomas, 2004;Agnoli et al, 2006). To test the effectiveness of mini-Tn5CmlacZYA, it was used to generate mutants of 715j that were deficient in production of both siderophores (Orb 2 Pch 2 phenotype).…”
Section: Construction Of New Reporter Transposons For Use In Burkholdmentioning
confidence: 99%
See 1 more Smart Citation